+0  
 
+1
165
2
avatar+1405 

Help Me, please.

 

Solve for g

 

h=\(\sqrt{\frac{g^2}{d}-5t}-1\)

 Mar 4, 2018

Best Answer 

 #1
avatar+7347 
+2

\(h=\sqrt{\frac{g^2}{d}-5t}-1\)

                                          Add  1  to both sides of the equation.

\(h+1=\sqrt{\frac{g^2}{d}-5t}\)

                                          Square both sides of the equation.

\((h+1)^2=\frac{g^2}{d}-5t\)

                                          Add  5t  to both sides.

\((h+1)^2+5t=\frac{g^2}{d}\)

                                                Multiply both sides by  d .

\(d[(h+1)^2+5t]=g^2\)

                                                Take the ± square root of both sides.

\(±\sqrt{d[(h+1)^2+5t]}=g \\~\\ g=±\sqrt{d[(h+1)^2+5t]}\)

.
 Mar 4, 2018
 #1
avatar+7347 
+2
Best Answer

\(h=\sqrt{\frac{g^2}{d}-5t}-1\)

                                          Add  1  to both sides of the equation.

\(h+1=\sqrt{\frac{g^2}{d}-5t}\)

                                          Square both sides of the equation.

\((h+1)^2=\frac{g^2}{d}-5t\)

                                          Add  5t  to both sides.

\((h+1)^2+5t=\frac{g^2}{d}\)

                                                Multiply both sides by  d .

\(d[(h+1)^2+5t]=g^2\)

                                                Take the ± square root of both sides.

\(±\sqrt{d[(h+1)^2+5t]}=g \\~\\ g=±\sqrt{d[(h+1)^2+5t]}\)

hectictar Mar 4, 2018
 #2
avatar+1405 
+2

Thank you!!

 Mar 4, 2018

13 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.